Sonographically Identified Echogenic Renal Masses Up to 1 cm in Size Are So Rarely Malignant They Can Be Safely Ignored. (6th January 2016) - Itani, Malak; Pandya, Amit; Bude, Ronald O.
Abstract : Objectives: The purpose of this study was to determine whether small echogenic renal masses up to 1 cm in size incidentally detected by sonography are rarely malignant and thus do not need further workup. Methods: We reviewed approximately 13, 600 reports of all abdominal sonographic examinations performed between November 2001 and October 2007 that identified a small echogenic mass in a kidney. Patients with known malignancy of any kind, tuberous sclerosis, lesions larger than 1.0 cm, lesions with heterogeneous echogenicity, and lesions with posterior ring‐down artifacts or posterior acoustic shadowing were excluded. All patients without magnetic resonance imaging or computed tomographic scans that completely characterized the lesions were excluded unless a follow‐up study (sonography, magnetic resonance imaging, or contrast‐enhanced computed tomography) at least 5 years later was available for comparison to prove that the lesion was benign. Results: A total of 120 lesions in 111 patients satisfied the inclusion criteria. Lesion sizes were 0 to 5 mm (n = 16) and 6 to 10 mm (n = 104). Of these, 54 lesions were characterized as definitely benign (47 angiomyolipomas and 7 other benign entities: calcifications in stones or within a cyst or calyx and cysts that were either simple on follow‐up studies or complicated with hemorrhagic or proteinaceous content). For the remaining 66 lesions, follow‐up results after at least 5 years were normal in 24 cases (which meant that the lesion was no longer visible), and the remaining 42 lesions were stable in size. The mean duration of follow‐up for these 66 lesions was 7.4 years. Conclusions: Small echogenic renal masses up to 1 cm in size that fulfill our study criteria are so likely to be benign that they can be safely ignored.